ANCAMAN SIBER DI TENGAH PANDEMI COVID-19 : TINJAUAN TERHADAP KEAMANAN NON-TRADISIONAL DAN KEAMANAN SIBER DI INDONESIA - Al Bahits Annef (Jurusan Ilmu Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Sriwijaya, 2021)
Several policies made by country during pandemic related to restriction and prohibition of public mobility implicated to cyberspace activities. Internet Users in Indonesia increased significantly by 17% in 2020 compared to 2019. Internet Users escalation during pandemic reciprocal with the rise of cyberattacks. By using qualitative methods, this paper aims to explain the phenomenon using two approaches, non-traditional security and cybersecurity. The author's findings show that cyberattacks in Indonesia elevated by 5 times in 2020. Some of these cyberattacks include phishing emails, ransomware and disinformation. These cyberattacks potentially threaten human security in various sectors such as personal, community, health, and economic security. Author also tries to elaborate the cyberattack with the National Cyber and Crypto Agency’s (BSSN) responses as a state entity.